Seedling growth and water relations of three Cedrela species sourced from five provenances: response to simulated rainfall reductions - Ruiz, Verónica Eugenia; Meloni, Diego A.; Fornes, Luis Fernando; Ordano, Mariano Andrés; Hilal, Mirna; Prado, Fernando Eduardo (2018)
The effects of different simulated rainfall regimes on water relations, growth, and biomass production and allocation of five provenances of Cedrela fissilis, C. saltensis and C. balansae were assessed in a pot-grown seedling experiment in greenhouse under uncontrolled conditions. Four simulated rainfall regimes were applied: 600 mm year−1 (severe water deficit), 800 mm year−1 (mild water deficit), 1,000 mm year−1 (mild wet), and 1,200 mm year−1 (well-watered) used as control. Provenances were compared in terms of water relations (midday leaf water potential, Ψ md and relative water content, RWC), growth (root, shoot and leaf length, neck diameter), growth rate (shoot- and neck growth rate, SGR and NGR), biomass production (root, shoot and leaf dry weight), and biomass allocation (root:shoot ratio, RSR). Multivariate analyses revealed that water relations differed significantly under all simulated rainfall treatments by means of several variables throughout time. Effects of species × treatment, and provenance nested within species × treatment interactions significantly were important. SGR and RSR also were important to explain differences in Ψ md and RWC between treatments and provenances. Broadly C. balansae and C. saltensis provenances seem to display a better performance than C. fissilis provenances under severe water deficit only. However, despite differences between provenances, it was not possible to clearly separate them according to their origin, based on water relations and growth performance. Even though the results of this study performed on pot-grown seedlings are based on relatively few observations and require additional confirmation, they allow an opportunity for speculation on the factors that are related to intraspecific variations that are likely to occur during the growth of seedlings from different geographical sites in field condition.